Pope and Devil : the Vatican's archives and the Third Reich - Wolf, Hubert 1959- (Belknap Press of Harvard University Press, 2010)
In rich detail, Wolf presents astonishing findings from the recently opened Vatican archives--discoveries that clarify the relations between National Socialism and the Vatican. He illuminates the thinking of the popes, cardinals, and bishops who saw themselves in a historic struggle against evil. --from publisher description